Rancang Bangun Sistem Informasi Pembelian Bahan Baku Pada PT. Herba Medica Lestari Dengan Metode Waterfall - Wati Erawati; Panji Madya Ramdani (Journal of Information System Research (JOSH), 2019)
At present the development of information technology is growing rapidly. As for many companies that use computers to spend up and simplify human work. PT. Herba Medica Lestari is a company engaged in the food and beverage industry that requires information system to support company needs. For the reason, the author tries to make a research regarding the purchase accounting information system at PT. Herba Medica Lestari which is currently not computerized as an alternative problem solving and as an auxiliary media that can process large andafast amounts of purchase anda storage data compared to paper media. Therefor with a computerized system better than a manual system, so that the purchasing system can run more effectively and efficiently, to make it better than the previous system